2423. Effectiveness and Safety of Ceftolozane/Tazobactam (TOL/TAZ) Use for Carbapenem-Resistant Pseudomonas Infections in Children. (26th November 2018) - Molloy, Leah; Abdulhamid, Ibrahim; Srivastava, Ruma; Ang, Jocelyn
Abstract: Background: Evidence for ceftolozane/tazobactam use in children is limited. We describe herein the outcomes of children treated with TOL/TAZ for various types of infections caused by carbapenem-resistant Pseudomonas aeruginosa (CR-PA). Methods: Retrospective analysis of children who received TOL/TAZ while hospitalized from 2014 to 2017. Clinical and microbiological outcomes and safety data were analyzed. Results: 8 children received TOL/TAZ for CR-PA infections (table): 3 cystic fibrosis (CF) exacerbations, 2 ventilator-associated pneumonia (VAP), 1 tracheitis, 1 chronic osteomyelitis (OM), 1 complicated intra-abdominal infection with urinary tract infection (cIAI/cUTI). All initial isolates were susceptible to TOL/TAZ per E-test. Creatinine clearance (CrCl) >90 mL/minute in all patients. Median total length of stay (LOS) was 73 days (d) (range 11–221) and median inpatient duration of TOL/TAZ was 13.5 d (range 5–61). One patient died from causes unrelated to infection; all other patients achieved clinical cure and TOL/TAZ was well tolerated. One patient experienced a slight increase in liver function tests that required dose reduction. 3 children received multiple courses (range: 2–8) for CF exacerbations. TOL/TAZ-resistant PA was detected in 1 patient after 2 months of therapy for OM. TOL/TAZ intermediately susceptible PA was detected in 1 patient after 7 courses of therapy for CF exacerbation, though subsequent cultures grew TOL/TAZ susceptible PA. Conclusion: TOL/TAZ was effective in treating various CR-PA infections. Therapy was well tolerated with no significant adverse events. Reduced TOL/TAZ susceptibility after prolonged or repeated courses was observed and presents potential opportunities for dose optimization and antimicrobial stewardship. Disclosures: All authors: No reported disclosures.